Economic Costs of Cardiovascular Diseases in Poland Estimates for 2015–2017 Years - Mela, Aneta; Rdzanek, Elżbieta; Poniatowski, Łukasz A.; Jaroszyński, Janusz; Furtak-Niczyporuk, Marzena; Gałązka-Sobotka, Małgorzata; Olejniczak, Dominik; Niewada, Maciej; Staniszewska, Anna (Frontiers in Pharmacology, 2020)
Background: The cardiovascular diseases are associated with growing public and private expenditure on healthcare regardless geographic region. Therefore, it become essential to accurately estimate the overall societal costs of, both direct and indirect from points of view including patients, caregivers and employers. Research design: This paper aims to measure the direct and indirect cost of cardiovascular diseases, in Poland for 2015-2017. Direct costs related to the treatment of cardiovascular diseases in Poland are calculated based on data available in the public domain. We use a modified human capital approach and unique dataset provided by the Social Security institution in Poland and the Polish Central Statistical Office. Results: Cardiovascular diseases related burden in Poland is significant. This study revealed that direct and indirect costs of cardiovascular diseases in 2015-2017 fluctuate between approximately 34.9 bn PLN (8.2 bn EUR) and more than 40.9 bn PLN (9.6 bn EUR). Total direct cost amounts to approximately 6.1 bn PLN (1.4 bn EUR) (16%) and the total indirect cost amounts to approximately 31.3 bn PLN (7.3 bn EUR) (84%). Conclusions: Collectively, estimated direct and indirect cost of cardiovascular diseases can constitute useful input for economic impact assessments of public health programs and health technology analyses.